A Unique Visual Attention Profile Associated With the FMR1 Premutation - Winston, Molly; Nayar, Kritika; Landau, Emily; Maltman, Nell; Sideris, John; Zhou, Lili; Sharp, Kevin; Berry-Kravis, Elizabeth; Losh, Molly (Frontiers in Genetics, 2021)
Atypical visual attention patterns have been observed among carriers of the FMR1 premutation (PM), with some similarities to visual attention patterns observed in autism spectrum disorder (ASD) and among clinically unaffected relatives of individuals with ASD. Patterns of visual attention could constitute biomarkers that can help to inform the neurocognitive profile of the PM, and that potentially span diagnostic boundaries. This study examined patterns of eye movement across an array of fixation measurements from three distinct eye-tracking tasks in order to investigate potentially overlapping profiles of visual attention among PM carriers, ASD parents, and parent controls. Logistic regression analyses were conducted to examine whether variables constituting a PM-specific looking profile were able to effectively predict group membership. Participants included 65 PM female carriers, 188 ASD parents, and 84 parent controls. Analyses of fixations across the eye-tracking tasks, and their corresponding areas of interest, revealed a distinct visual attention pattern in carriers of the FMR1 PM, characterized by increased fixations on the mouth when viewing faces, more intense focus on bodies in socially complex scenes, and decreased fixations on salient characters and faces while narrating a wordless picturebook. This set of variables was able to successfully differentiate individuals with the PM from controls (Sensitivity=.76, Specificity=.85, Accuracy=.77) as well as from ASD parents (Sensitivity=.66, Specificity=.66, Accuracy=.72), but did not show a strong distinction between ASD parents and controls (Accuracy=.62), indicating that this set of variables comprises a profile that is unique to PM carriers. Regarding predictive power, fixations towards the mouth when viewing faces was able to differentiate PM carriers from both ASD Parents and controls, whereas fixations towards other social stimuli did not differentiate PM carriers from ASD parents, highlighting some overlap in visual attention patterns that could point toward shared neurobiological mechanisms. Results demonstrate a profile of visual attention that appears strongly associated with the FMR1 PM in women, and may constitute a meaningful biomarker.